Mushroom Intoxication in Türkiye: A Nationwide Cohort Study Based on Demographic Trends, Seasonal Variations, and the Impact of Climate Change on Incidence - Turan Gökçe, Dilara; Arı, Derya; Ata, Naim; Gökcan, Hale; İdilman, Ramazan; Ülgü, Mustafa Mahir; Harputluoglu, Murat; Akarsu, Mesut; Karasu, Zeki; Ayvalı, Mustafa Okan; Birinci, Şuayip; Akdoğan Kayhan, Meral (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Mushroom intoxication poses a considerable public health risk due to its potential for severe toxicity and fatality. This study aims to investigate demographic trends, diagnostic locations, and mortality rates of patients with mushroom intoxication. Materials and Methods: This retrospective cohort study utilized data from the National Electronic Database of the Turkish Ministry of Health. The study focused on patients without chronic liver disease or prior liver transplantation presenting with mushroom intoxication between 2018 and 2023. Demographic information, diagnostic locations, and mortality rates were analyzed, considering a six-year period to ensure even seasonal distribution. Results: Among 30459 individuals admitted with mushroom intoxication, 44.75% were male, with a mean age of 45.84 years. The Black Sea, Marmara, and Central Anatolia regions had the highest number of cases, with specific cities like Tokat, Bolu, Yozgat, and Kastamonu having the highest rates per 100,000 population in 2022. Mushroom intoxication predominantly occurred in May, June, October, and November. Hospitalization occurred in 8.9% of cases, with a 6.6% mortality rate within 90 days and 1.3% progressing to liver transplantation. Notably, mushroom intoxication cases increased by 130% in the first half of 2023, particularly in May and June, correlating with increased rainfall. Conclusion: Mushroom intoxication is a serious public health issue, with morbidity and mortality influenced by climate factors. The study highlights a significant increase in cases in the first half of 2023, potentially linked to heightened rainfall and climate change. Cite this article as: Turan Gökçe D, Arı D, Ata N, et al. Mushroom intoxication in Türkiye: a nationwide cohort study based on demographic trends, seasonal variations, and the impact of climate change on incidence. Turk J Gastroenterol. 2025;36(1):61-66.